2003
DOI: 10.1002/pola.10618
|View full text |Cite
|
Sign up to set email alerts
|

Bicyclobutanes and cyclobutenes: Unusual carbocyclic monomers

Abstract: ABSTRACT:Bicyclobutanes and cyclobutenes substituted with electron-attracting groups represent novel classes of reactive monomers. They readily undergo free-radical and anionic polymerizations to give high polymers consisting of 1,3-and 1,2-enchained cyclobutane rings, respectively.They also copolymerize readily with conventional vinyl monomers. These polymers display numerous attractive properties in comparison with their vinyl counterparts, including enhanced thermal stability, superior optical properties, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“…C Labeling Experiments to Explore C(sp 3 )−C(sp 3 ) Bond Formation. To determine whether reversible C(sp 3 )− C(sp 3 ) is occurring in the absence of added ligand, a 13 Clabeling experiment was conducted whereby a benzene-d 6 solution of ( Me PDI)Fe(s-trans-η 4 -C 4 H 6 ) was treated with 3 equiv of 13 C 2 H 4 . Oxidative cyclization quantitatively generated the S = 0, (PDI)Fe metallacycloheptene as judged by 1 H and 13 C{ 1 H} NMR spectroscopy (Scheme 8A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C Labeling Experiments to Explore C(sp 3 )−C(sp 3 ) Bond Formation. To determine whether reversible C(sp 3 )− C(sp 3 ) is occurring in the absence of added ligand, a 13 Clabeling experiment was conducted whereby a benzene-d 6 solution of ( Me PDI)Fe(s-trans-η 4 -C 4 H 6 ) was treated with 3 equiv of 13 C 2 H 4 . Oxidative cyclization quantitatively generated the S = 0, (PDI)Fe metallacycloheptene as judged by 1 H and 13 C{ 1 H} NMR spectroscopy (Scheme 8A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…An excess of ethylene was used to suppress competing retro-[2 + 2] cyclization of the formed metallocycle that complicated interpretation of the spectroscopic data, and previous studies have shown that excess ethylene does not trigger vinylcyclobutane formation. 17 Examination of the metallocyclic product by 13 C NMR spectroscopy established incorporation of the isotopic label in three positions − α, β, and γ-carbons−of the metallocycle. This result is inconsistent with a static metallocycle, where oxidative cyclization between butadiene and ethylene would place the 13 C label exclusively at the α and β positions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In most cases, polymerization of the BCB was observed. 15 At this stage, we decided to explore an alternative approach that would involve triplet energy transfer (Scheme 2B). In this scenario, the substituent bound to the BCB should be capable of being sensitized.…”
Section: Scheme 1 Cycloaddition Approaches Towards [211]-bicyclohexanesmentioning
confidence: 99%
“…The stereochemistry of ring-opening polymerizations of episulfides, lactones, lactides, N-carboxy-a-amino acid anhydrides, and other monomers has been studied but not as extensively as the epoxides [Boucard et al, 2001;Chatani et al, 1979;Duda and Penczek, 2001;Elias et al, 1975;Guerin et al, 1980;Hall and Padias, 2003;Imanishi and Hashimoto, 1979;Inoue, 1976;Ovitt and Coates, 2000;Spassky et al, 1978;Zhang et al, 1990].…”
Section: LVIIImentioning
confidence: 99%